EMPIRICAL ASSESSMENT ON SIMULATION-BASED LEARNING FOR HIGHER ELECTRONICS IN SETTING UP GREENHOUSE AUTOMATION - Pardiñan, Eric G (Journal of Agriculture and Technology Management; Vol 25 No 1 (2022): Vol 25 No 1 (2022): Journal of Agriculture and Technology Management (JATM) Volume 25 January - June 2022 Issue, 2022)
Many parts of our lives are now heavily influenced by technology. Technology is an essential complement to creative instructional techniques. Due to multimedia and network interactivity, students are taking on new roles as participants rather than observers in their learning process. The study's purpose was to evaluate how pleased individuals were with simulation software and whether they would utilize it as a foundation for technology adoption in higher education, mainly teaching higher electronics that deals with automation processes such as greenhouse automation. The study utilized the Modified TAM and DeLone & McLean IS Success Model in determining the respondents' acceptance of simulation- based learning for instruction. Functional constructs from the Modified TAM and D&M IS Model were then validated based on the product quality model ISO/IEC 25010. The research results using Confirmatory Factor Analysis (CFA), Kaiser – Meyer – Olkin (KMO), Cronbach Alpha, and Bartlett's test validated the study's consistency. The majority of the respondents agreed that simulation-based learning is acceptable. The behavioral intention and attitude toward using technology were confirmed by the acceptance of using a simulation software platform in teaching-learning higher electronics. On the other hand, the study recommended that needs be assessed, that suitable orientation be provided, and that technology be evaluated. Since technology is continuously improving and becoming more accessible, further studies incorporating a bigger pool of specialists from diverse sectors and continuous research may be advantageous.